High-frequency power loss mechanisms in ultra-thin amorphous ribbons - Stamenov, Plamen (My University, 2021)
Soft magnetic amorphous materials with ultra-low power loss are highly desirable for high-frequency drive applications. The present work demonstrates the high-frequency power loss performance and underlying loss mechanisms in ultra-thin amorphous alloys. This is achieved by rapid-quenching amorphous alloys of Co-, CoFe- and Fe-rich systems, investigating their amorphous atomic structure, quantifying the saturation magnetostriction constants (λs ), imaging magnetic domains at remanent magnetization, analyzing magnetization reversal from various magnetization levels, and finally, investigating the material loss performance over a broad frequency range (f = 50 kHz–2 MHz) at various excitation levels (B m = 25–100 mT). The ultra-high performance of ultra- thin Co-rich amorphous ribbons, as compared to CoFe- and Fe-rich alloys, was attributed to the significantly low eddy current loss, due to the reduced thickness, and a minimal amount of excess loss, owning to minimal magnetoelastic contributions and magnetization reversal by rotation. The underlying loss mechanisms were analyzed by decomposing material loss into primary components and identifying the magnetization reversal mechanisms using minor hysteresis loops. In the Co-rich amorphous alloys, we suggest that magnetization re- versal by rotation dominates, at least at low excitations, while in CoFe- and Fe-rich alloys domain wall dis- placement prevails and contributes significantly to the excess loss up to the MHz frequency range. Magnetization reversal by rotation in Co-rich alloys could be attributed to the zero/near-zero λs , and eventually low residual stress, leading to a homogeneous magnetic domain structure, as compared to the inhomogeneous “fingerprint- like” complex domains in highly magnetostrictive CoFe-rich alloys.
PUBLISHED
Keywords: amorphous atomic structure; Co-rich amorphous ribbons; ultra-low power loss; Excess loss; Eddy current loss; Materials loss mechanisms; High-frequency applications; Ultra-thin ribbons; Amorphous alloys; Soft magnetic materials